Anomalous coagulation factors in non-arteritic anterior ischemic optic neuropathy with central retinal vein occlusion: A case report. Issue 15 (April 2018) - Kim, Ji Hong; Kang, Min Ho; Seong, Mincheol; Cho, Heeyoon; Shin, Yong Un
Abstract: Rationale: Non-arteritic anterior ischemic optic neuropathy (NAION) is characterized by sudden, painless visual loss and optic disc edema. NAION occurs mainly in the presence of cardiovascular disease and hypercoagulability, mainly in patients over 50 years of age. We experienced a case of NAION associated with central retinal vein occlusion (CRVO) in a young man with no underlying disease. Patient concerns: A 46-year-old man was referred to our clinic following a sudden loss of vision in his right eye. The patient exhibited no underlying disease and reported no ongoing medication. Significant visual loss and visual disturbance of the right eye were observed. The pupil of the right eye was enlarged and an afferent pupillary defect was observed. On fundus examination, retinal hemorrhage was observed in the peripheral retina; macular edema was observed in optical coherence tomography analysis. However, optic disc edema was not evident. No abnormal findings were found in routine blood tests for hypercoagulability. After 3 days of steroid intravenous injection, macular edema disappeared and visual acuity was improved, but optic disc edema began to appear. One week later, optic disc edema was evident and visual acuity was significantly reduced; thus, the patient was diagnosed with NAION. In fluorescein angiography, peripheral retinal ischemia was observed, suggesting that CRVO was complicated. Blood tests, including analysis of coagulation factors, were performed again, showing that coagulation factors IX and XI were increased. Diagnoses: Anomalous coagulation factors in non-arteritic anterior ischemic optic neuropathy with central retinal vein occlusion. Interventions: Systemic steroids were administered. Outcomes: One month later, optic disc edema and retinal hemorrhage gradually diminished and eventually disappeared; however, visual acuity did not recover. Conclusion: In young patients without underlying disease, cases of NAION require careful screening for coagulation disorders. Even if there is no abnormality in the test for routine coagulation status, it may be necessary to confirm a coagulation defect through an additional coagulation factor assay.